ChemInform Abstract: Ruthenium‐Catalyzed Transfer‐Hydrogenative Cyclization of 1, 6‐Diynes with Hantzsch 1, 4‐Dihydropyridine as a H2 Surrogate. Issue 5 (4th February 2014) - Yamamoto, Yoshihiko; Mori, Shota; Shibuya, Masatoshi
Abstract A hydrogenative cyclization of 1, 6‐diynes is developed using Ru‐catalysis and the Hantzsch 1, 4‐dihydropyridine as hydrogen source.